2018
DOI: 10.21608/jsrs.2018.25535
|View full text |Cite
|
Sign up to set email alerts
|

Possible action of grape seed oil on brain toxicity induced by methomyl or imidacloprid of male rats.

Abstract: The present study was planned to investigate the effect of methomyl or imidacloprid on the brain of male rats. The effect grape seeds oil as an antioxidant was also evaluated. Animals were administered orally with 1/10 and 1/20 of LD 50 methomyl and imidacloprid with 17 and 450 mg /kg bw for four and eight weeks. Grape seeds oil with 4 ml/kg b.wt. was used for protection from methomyl and imidacloprid toxicity. Brain cortex and hippocampus oxidative stress (glutathione S transferase GST, glutathione peroxidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 84 publications
2
1
0
Order By: Relevance
“…The recoded inductions in the activities of ATP-ase in serum, brain, liver, heart and wing muscles were higher than the control by1.47-2.48, 1.85-2.87, 1.43-2.04, 1.32-2.97, and 3.19 fold following treatment with IMI for 1-28, 14-28, 1-28, 1-14, and 28 days every other day, respectively. The present results are in parallel with the results of Abdel-Haleem et al (2018) who found that IMI and thiamethoxam increased the activities of ATP-ase in adult house ies, while the activity was inhibited in rat brain and erythrocyte following treatment with 45 and 90 mg/kg of IMI (Lonare et al 2014;Moeen et al 2018). Moreover, ATP-ase enzyme was found to be altered after IMI exposure at different levels depending on each tissue demand.…”
Section: Effect On Atp-asesupporting
confidence: 92%
See 2 more Smart Citations
“…The recoded inductions in the activities of ATP-ase in serum, brain, liver, heart and wing muscles were higher than the control by1.47-2.48, 1.85-2.87, 1.43-2.04, 1.32-2.97, and 3.19 fold following treatment with IMI for 1-28, 14-28, 1-28, 1-14, and 28 days every other day, respectively. The present results are in parallel with the results of Abdel-Haleem et al (2018) who found that IMI and thiamethoxam increased the activities of ATP-ase in adult house ies, while the activity was inhibited in rat brain and erythrocyte following treatment with 45 and 90 mg/kg of IMI (Lonare et al 2014;Moeen et al 2018). Moreover, ATP-ase enzyme was found to be altered after IMI exposure at different levels depending on each tissue demand.…”
Section: Effect On Atp-asesupporting
confidence: 92%
“…Pigeons were found to have different GST activities in different tissues and arranged as follows: kidney > liver > testes > brain > lung > heart (Kumar et al 1980). The present results are in parallel with the results of many investigators, where IMI signi cantly elevated the GST activity in mice (El-Gendy et al 2010) and rat (Moeen et al 2018) suggesting that this pesticide exerts its toxic effect by the induction of oxidative stress. However, when male rats were orally administered with IMI, a non-signi cant decreases in the brain GST activity was recorded following 4 weeks of treatment (Lonare et al 2014).…”
Section: Effect Of Imi On Glutathione S-transferase (Gst)supporting
confidence: 92%
See 1 more Smart Citation